Reposisi Majelis Permusyawaratan Rakyat (MPR) dan Implikasinya terhadap Kedudukan TAP MPR/S Pasca Amandemen UUD 1945 - Eko Riyadi (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Four times the 1945 amendments made by the Assembly since 1999-2002 has been overhauling the structure and organization of state administration Indonesia. Change is also happening to the state institutions. MPR no longer a State Agency, but a State Agency such as the House of Representatives, the President and others. MPR status changes bring serious impact on the legal product MPR MPR. In addition, the position of the Assembly according to post-amendment UUDN RI very weak and tends to only as a complement strultur state administration bodies of the republic of Indonesia. This paper examines the repositioning of the Assembly was about to post the 1945 amendments and the implications of repositioning of the MPR to MPR (s) in khirarki legislation in Indonesia.